2017
DOI: 10.4025/actascitechnol.v39i4.30511
|View full text |Cite
|
Sign up to set email alerts
|

<b>Ergonomic adjustments on a website from the usability of functions: Can deficits impair functionalities?

Abstract: Current study assesses whether deficits and usability of ergonomics impair the functionality of a university website. The concepts of functionality, usability and ergonomics were foregrounded by contextualizing them within a university profile. Later, a satisfaction survey was proposed to users to measure the satisfaction in the use of the website and to map the problems in usability. In addition, an ergonomic inspection was performed on the site by applying Bastien and Scapin´s ergonomic criteria. After analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The loading time is only marginally important to attract more backers and not significant to increase funding. This suggests that an additional website must have a good user experience to improve SEO 10 (Lewandowski et al, 2021) and facilitate user navigation (Laperuta et al, 2017). According to Wang and Emurian (2005), people's cognitive and emotional responses are influenced by their website perceptions and experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loading time is only marginally important to attract more backers and not significant to increase funding. This suggests that an additional website must have a good user experience to improve SEO 10 (Lewandowski et al, 2021) and facilitate user navigation (Laperuta et al, 2017). According to Wang and Emurian (2005), people's cognitive and emotional responses are influenced by their website perceptions and experiences.…”
Section: Discussionmentioning
confidence: 99%
“…It is also imperative that the website follows specific ergonomic recommendations. As demonstrated by Laperuta et al (2017), in order to be attractive, a website should have a short loading time and offer a good user experience (i.e., integrate all functionalities that facilitate user navigation). If a webpage takes a long time to load, users may quit it, or stop using a website altogether (Pourghassemi et al, 2019).…”
Section: The Role Of An Additional Websitementioning
confidence: 99%
“…It seems that modifying and redesigning the system based on ergonomic principles, can be useful in improving the employee's performance. A review of related literatures, suggested that ergonomic principles in the designing of websites, such as information grouping based on format, feedback, readability, conclusion, minimum activity, flexibility and the user's experience, play an important role in the usability of websites (15). The results of a study by Agharezaei and his colleagues, showed that the laboratory information system used in some hospitals of the country, has many usability problems and if it is not solved, it will lead to performance deficiency, error increase, and user confusion (16).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding evaluating the platform's technical quality, most studies evaluated the two general aspects of the functional effectiveness and technical aesthetics of online platforms or websites and then proposed enhancement in operation technology and interface design. Reportedly, improving online platforms helps to increase user satisfaction and user application continuity (Ng, 2014;Laperuta et al, 2017;Liu et al, 2017;Manzoor et al, 2018;Mousavilou and Oskouei, 2018). Santos et al (2016Santos et al ( , 2019 followed the five principles, namely, multimedia quality, content, navigation, access speed, and interaction in graphic design, to measure user satisfaction in online learning websites.…”
Section: Technical Qualitymentioning
confidence: 99%